Criminal procedural responsibility under the new 2014 criminal-procedural code of the Republic of Kazakhstan - Mitskaya E. V., Talyshev M. Z. (Interactive science, 2017)
the subject of the study is the institution of criminal procedural liability. Sanctions of criminal procedural liability, namely a monetary redress, received the first legislative consolidation in the new Criminal Procedure Code of Kazakhstan. Who the pecuniary punishment is applied to is fixed in the article 159 of Code of Criminal Procedure of the Republic of Kazakhstan. The size and procedural order of its application is regulated by the article 160 of Code of Criminal Procedure of the Republic of Kazakhstan. The authors analyze the introduction of the judicial mechanism of pecuniary punishment and the existence of the Code of Administrative Offenses on the monetary redress expressed in the form of an administrative fine and conclude that it is difficult to differentiate the sanctions of criminal procedural responsibility in the form of a monetary redress and an administrative fine for the commission of criminal procedural violations. The authors present their own arguments to address the duality of application of the Code of Criminal Procedure and the Code of Administrative Offenses to bring to criminal procedure responsibility and administrative responsibility for the same criminal procedural violations.
Keywords: уголовно-процессуальное законодательство; уголовно-процессуальная ответственность; уголовно-процессуальные нарушения; административный штраф; денежное взыскание; criminal procedure legislation; criminal procedural liability; criminal procedural violations; administrative fine; monetary redress